DIGITALISASI PELAYANAN PUBLIK PEMERINTAH SUMATRA UTARA MELALUI WEBSITE WWW.SUMUTPROV.GO.ID: DIGITALISASI PELAYANAN PUBLIK PEMERINTAH SUMATRA UTARA MELALUI WEBSITE WWW.SUMUTPROV.GO.ID - Saragih, Jopinus (Universitas Serang Raya, 2024)
ABSTRACT This research purpose is to describe about the implementation of digitalization of North Sumatra Government public services through the website sumutprov.go.id. Hoped that this results can contribute to further understanding regarding the implementation of digitalization of public services at the provincial level, especially in North Sumatra. It is also hoped that give the recommendations from this research can serve as a guide for the government and related agencies in improving the quality of public services through digital platforms. This research method use a qualitative descriptive, which is to describe phenomena in a real context, without manipulating variables or producing statistical generalizations. The results show that the digitalization on public services via the website sumutprov.go.id has shown significant progress in providing more efficient, accessible and transparent services for the community. By displaying 18 varied service menus, this site succeeds in providing clear information and in accordance with the theme of each menu, make visitors easy to access the information they need. Keywords : Management, Public Services and Digitalization